Análise evolutiva baseada no genoma de Pasteurella multocida proveniente de isolados veterinários - Raquel Enma Hurtado Castillo (2019)
Pasteurella multocida is a commensal and opportunistic pathogen that causes several diseases such as snuffles, pneumonia, atrophic rhinitis, fowl cholera and hemorrhagic septicemia in different hosts. These diseases cause a high rate of morbidity and mortality, causing important economic loss worldwide. In Peru, P. multocida is a mean agent of pneumonic infection, with a high mortality rate in neonatal alpacas in the seasons of icy. This represents a major problem since the production of alpacas is one of the main economic resources from the Andes region. In this context, knowledge of genomic characteristics from P. multocida species is essential for the development of future strategies for the control and prevention of these diseases. For this reason, the UNMSM strain isolated from an alpaca with pneumonia was sequenced and 22 P. multocida strains were retrieved from the NCBI database. In this case, to decipher the genetic diversity and adaptive process of P. multocida, this work aimed to perform phylogenomic and pan genomic analyses of isolates from distinct diseases and hosts. Analysis of positive selection, prediction of genomic islands and accessory genome were performed in the phenotype established phenotypic groups. As a result, the pathogenicity of the UNMSM strain was evidenced due to the presence of the main virulence genes of the species and the presence of pathogenicity islands. However, phylogenetic analysis has shown that the UNMSM strain diverges from other lineages in the pneumonia group. Analysis of the diversity based on the nucleotide/aminoacid phylogeny and presence and absence of genes show the agreement of the clustering of lineages from established phenotypic groups. Analysis of diversity by phylogeny based on the presence and absence of genes showed greater variability in the same group. Notably, the accessory genes encode proteins associated with metabolism and transport of carbohydrates, aminoacids, cell wall and membrane biogenesis, and hypothetical proteins. The presence of these functional groups as part of the accessory genome suggest the importance in the adaptation process, suggesting their fixation in the genome through selective pressure. Positive selection analysis identified genes under selection, relevant in host interaction but are not involved in the pathogen adaptation process. In conclusion, the presence of genomic islands and determinate strains would play a crucial role in host/disease predilection. Transcriptional and genomic analyzes may provide new information about the essential role of horizontal transfer events and single nucleotide polymorphisms involved in the diversification and understanding of the mechanisms of P. multocida adaptation.